Investigating the Distance to Crime for Offenders With Mental Illness: How Routine Is Routine?. (May 2019) - Zawisza, Thomas; Frailing, Kelly
Research consistently demonstrates that offenders do not travel far to crime. Although this finding has been observed across different types of offending and offenders, one group rarely examined within this paradigm is offenders with mental illness (OWMI). We calculated the distance to crime for a group of offenders with a documented mental illness and compared that distance to those in other publications for other samples. We found that our sample of OWMI traveled about the same and in some cases shorter distances to crime than other offenders. Although this study has limitations, we believe it nevertheless lends support to the environmental criminology paradigm and provides important policy implications, as well as questions for further research.